Seismic Site Characterization Using Horizontal-to-Vertical Spectral Ratio (HVSR) Analysis of Ambient Noise at Sukasari Village, Sumedang, West Java - Susetyo, Dimastian Hari; Jamaluddin , Jamaluddin; Rosandi, Yudi (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
Local geological conditions can significantly influence seismic wave amplification during earthquakes, particularly in regions composed of unconsolidated volcanic deposits. This study aims to characterize the seismic site conditions of Sukasari Village, Sumedang Regency, West Java, using the Horizontal-to-Vertical Spectral Ratio (HVSR) method based on ambient seismic noise measurements. A total of 72 microtremor measurement points were distributed across the study area to capture spatial variations in near-surface geological conditions. HVSR analysis was conducted to determine key parameters, including dominant frequency (), amplification factor (), dominant period (), and the seismic vulnerability index (). The results show that  values range from 1.1 to 19.1 Hz,  ranges from 0.058 to 1.788 s,  ranges from 1.4 to 7.3, and  ranges from 1.0 to 22.8, indicating significant variations in sediment thickness and subsurface stiffness across the study area. Areas characterized by low  values and high  and  are associated with thick unconsolidated sediments that have a higher potential for seismic wave amplification, whereas areas with high F₀ and low Kg correspond to compact volcanic formations with relatively stable ground conditions. These findings demonstrate that the HVSR method effectively identifies spatial variations in local site response and provides important information for seismic microzonation and earthquake-resilient land-use planning in Sukasari Village.